Desarrollo de un sistema para diagnóstico del consumo de energía, mediante los parámetros eléctricos en el bloque antiguo de la Universidad Técnica de Cotopaxi en el Campus la Matriz periodo 2020. - Bonilla Bonilla, Edwin Andrés (2020)
With the purpose of minimizing the ignorance of the electrical parameters in the facilities of the old block of the UTC. The development of an electrical parameter supervision system was proposed that will be implemented in the main distribution board of the old block of the Technical University of Cotopaxi (UTC) with the purpose of acquiring historical data in the period 2020, for the diagnosis of energy. and the maximum demand that exists. A monitoring and data acquisition system was installed through an energy meter and internet connection to view them anywhere through a virtual platform and an HMI. For the development of the data acquisition system, the quantitative approach, field and bibliographical research was used, a descriptive method that through the observation technique determined the necessary variables for the diagnosis of energy that each of the phases presents. of the main distribution board.